Changing Features of State Personnel Policy In Uzbekistan - Aliqulovich, Axmedov (Indonesian Journal Publisher, 2025)
Large-scale and intensive reforms are being implemented in the new Uzbekistan to form a free and strong civil society. This article is devoted to the issues of raising the potential of our people, which is entering a new stage of development, to higher heights by implementing fundamental reforms and major innovations in all areas, bringing our country to the ranks of developed countries, and establishing the most advanced democratic and free civil society in our country. The fact that the state personnel policy in Uzbekistan has changed at various stages over the past period, that these changes are closely related to the political, economic and social development of the country, and the main changing